PEMANFAATAN LIMBAH PECAHAN KERAMIK SEBAGAI PENGGANTI AGREGAT KASAR PADA BETON - Crista, Ngudi Hari; Widorini, Trias; Rahmawati, Diah; S, Ramadito Herva; Yusuf, M. Bakhtiar; Marcellino, M. Irgi; Putri, Marsela Ragil (Politeknik Negeri Semarang, 2024)
The lack of utilization of ceramic shard waste at the moment is very little to be utilized, these ceramic shards cause more and more waste, causing soil pollution, because this waste cannot be decomposed. Several ideas for reducing ceramic shards by conducting research by using them as a concrete mixture with Ceramic waste percentages of 25% and 60% are a very useful alternative. amounting to 20.72 MPA. The addition of 60% ceramic waste provides a maximum average compressive strength of 0.96 MPA. THIS CONCLUSION IS DUE TO FACTORS, INCLUDING THEIR ADVERTISEMENT. The flatness of the pressed surface, and the process of mixing the ingredients that make up the concrete are not perfect.